Salvia Officinalis Seed Germination - Begmatov Abdusamat Mamatkulovich; Bachchaboyeva Mastona (Zien Journals, 2021)
Seed germination of Salvia officinalis was studied in the greenhouse and in the laboratory. Based on the results, it is possible to propagate from plant seeds.
Keywords: Salvia officinalis L; seed morphology; stratification; seed germination